Radiological hazard assessment of natural radionuclides in soils of Udege Mbeki Mining Area, Nasarawa State, Nigeria - Osas, Eghaghe Stephen; Jude, Koffa Durojaiye; James, Eneye; James, Rabba Anthony; Vivian, Obaje Onechojo; Emmanuel, Echioda; Joseph, Aremu; Nafiu, Aliu Sadiq (Journal of Physics: Theories and Applications, 2024)
Mining involves excavating soil with radioactive materials, which may enter the food chain and harm humans. This study evaluated the risks of exposure to ionizing radiation from radium-226, potassium-40, and thorium-232 in Udege Mbeki mining area of Nasarawa State, Nigeria. Twenty-one (21) soil samples were randomly collected in the mining site. The activity concentration of 226Ra, 232Th, and 40K in the samples ranged from 12.7462-430.8147 Bq/kg, 38.4147-725.4748 Bq/kg, and 22.3092-395.5596 Bq/kg respectively. The estimated effective dose in the Udege mined site soil samples was 19.7538-330.3428 mSvy-1, with an average of 148.8091 mSvy-1 in the dump, 67.1197 mSvy-1 in the farmland, and 121.4909 in the surface soil. These values exceed ICRP's recommended reference level of 1mSvy-1 for public exposure and 20 mSvy-1 for workers. Thus, the mine is hazardous for both the public and workers. It is recommended that the implementation of a routine monitoring be implemented on the radiation levels in the mined tailings on a periodic basis, so as to keep track of the rise and fall in the radioactivity levels. This is necessary for a sensitization scheme to be put in place in order to educate the inhabitants of the area on the need for self-protection from the hazards of ionizing radiation as well as educating the workers on the necessity to follow the right procedure and use the necessary protective gears.